Risks of political stability of state (Journal of Philosophy Culture and Political Science, 2018)
The current situation in Kazakhstan is characterized as uncertain and risky having adverse circumstances caused first of all by the crisis of power. Risks of political stability can be caused by both quantitative and qualitative violations in the implementation of resources. Quantitative violations are situational and they can be overcome by the political system without changing its quality. Quality violations can escalate into a crisis that may indicate a need to change the manage of technology or changes in the political regime. Considered the risks of the political system of Kazakhstan are caused by the implementation of its internal policy. The frequency of occurrence of an event such as parliamentary crisis is the basis for determining the probability of risk.Key words: risks, political stability, stability, national interests, crisis of power.